2022
DOI: 10.1186/s13073-022-01142-7
|View full text |Cite
|
Sign up to set email alerts
|

Calculating variant penetrance from family history of disease and average family size in population-scale data

Abstract: Background Genetic penetrance is the probability of a phenotype when harbouring a particular pathogenic variant. Accurate penetrance estimates are important across biomedical fields including genetic counselling, disease research, and gene therapy. However, existing approaches for penetrance estimation require, for instance, large family pedigrees or availability of large databases of people affected and not affected by a disease. Methods We presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Within this premise, we sought to develop a human iPSC-based preclinical model that would allow us to functionally interrogate the interaction between neurotrauma, degeneration, and associated molecular pathology in the context of patient human ALS MNs. We selected to use MNs with a C9orf72 HRE on account of the wide range of clinical diversity associated with these patients [18][19][20][21][22][23], and implemented a custom built mechanical instrument that can deliver biofidelic stretch-based traumatic injury in vitro [47][48][49]. We found that our model faithfully recapitulated core tenets of C9orf72 ALS pathology in both a transient and persistent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this premise, we sought to develop a human iPSC-based preclinical model that would allow us to functionally interrogate the interaction between neurotrauma, degeneration, and associated molecular pathology in the context of patient human ALS MNs. We selected to use MNs with a C9orf72 HRE on account of the wide range of clinical diversity associated with these patients [18][19][20][21][22][23], and implemented a custom built mechanical instrument that can deliver biofidelic stretch-based traumatic injury in vitro [47][48][49]. We found that our model faithfully recapitulated core tenets of C9orf72 ALS pathology in both a transient and persistent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Patients carrying the C9orf72 HRE are characterized by a diverse clinical presentation with a subset of individuals exhibiting only ALS or only FTD symptoms, while others are diagnosed with both [7][8][9][10]. The age of onset for C9orf72 patients is also highly variable and can range between 40 to 90 years, while in rare cases C9-HRE carriers never exhibit disease symptoms [18][19][20][21][22][23]. While the length of the C9-HRE can range between tens to thousands of repeats, the age of onset does not definitively correlate with any specific C9-HRE associated pathology such as repeat length, prevalence of RNA foci or DPR aggregates [15,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…While a previous assessment of oligogenicity involving C9orf72 suggested the repeat expansion was sufficient to cause ALS alone 49 , our results suggested an increased risk from oligogenic events involving C9orf72 in comparison to C9orf72 singleton events. Oligogenic events could help explain the recent incomplete penetrance estimates of C9orf72 expansions 50 . Further, Ciura et al identified pathways by which the C9orf72 and ATXN2 pathogenic repeat expansions may genetically interact, suggesting an actual biological impact of oligogenicity involving C9orf72 in ALS pathogenesis 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of incomplete penetration observed in ALS may arise from the diverse pathogenic potential of variants, underscoring the complex nature of ALS genetics. An algorithm was used to calculate variant penetrance from family history of disease and average family size in population-scale data [ 64 ]. This complexity has led to the formulation of a series of hypotheses aimed at explaining such cases, especially those involving variants with a larger patient pool.…”
Section: Clinical Phenotypic Heterogeneitymentioning
confidence: 99%